The stepwise Indian–Eurasian collision and uplift of the Himalayan‐Tibetan plateau drove the diversification of high‐elevation Scytodes spiders. (8th July 2022) - Luo, Yufa; Li, Shuqiang
Abstract: The Cenozoic Indian–Eurasian collision and uplift of the Himalayan‐Tibetan Plateau (HTP) are among the most important geological events in the world. They have affected the diversification of regional biota of many taxonomic groups on and around the HTP. However, the exact timing and model of the collision and uplift events and speciation on and around the HTP are still in debate. The Himalayas group of Scytodes spitting spiders (Araneae: Scytodidae) are distributed at high elevations of the HTP and northern Indochina. Here, we reconstruct a dated molecular phylogeny for pan‐Himalayan Scytodes spiders, including the Himalayas group, with full geographical sampling of the species from the HTP and Indochina. We test a hypothesis to explain that the rich montane biodiversity of the region is uplift‐driven diversification—that orogeny drives rapid in situ speciation of the resident Scytodes lineages. Our findings revealed that the separation of the Himalayas clade from the Myanmar clade took place during the middle Oligocene, reflecting the final collision of India with Eurasia. The deep divergences among three clades (the Himalayas, the Myanmar and the Indochina clades) occurred from the middle Eocene to the middle Oligocene, corresponding to two early uplift events of the HTP. The evolutionary split between the Himalayas + Myanmar and Indochina clades were simultaneous with the rapid lateral extrusion of Indochina by the initial Himalayan uplift around the Eocene. This study highlights the importance of the diversification of dispersal‐limited, high‐elevation invertebrates as independent lines of evidence to reflect key tectonic events in the Himalayan‐Indochina region, supporting the stepwise model for the Indian–Eurasian collision and uplift of HTP.